Analisis Strategi Sumber Daya Manusia dalam Meningkatkan Retensi Karyawan: Studi Literatur pada Beberapa Korporasi Besar di Indonesia - Salsabila Ayu Arifia; Mohammad Sawaluddin; Fadali Rahman; Rachman Hakim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze human resource strategies in improving employee retention in several major corporations in Indonesia through a literature review approach. The research method used is a systematic literature review by examining various scientific articles, national journals, and relevant supporting documents published during the 2023–2025 period. Data were collected through literature searches from various sources and analyzed descriptively using a qualitative approach to identify human resource strategies that contribute to employee retention. The findings indicate that competency development through training, competitive compensation, career development, employee engagement, and the creation of a positive work environment and organizational culture have a significant role in increasing employee loyalty and commitment. The continuous implementation of human resource strategies can help companies retain qualified employees and enhance organizational competitiveness in an increasingly dynamic business environment.